PEMANFAATAN SIPUT GONGGONG SEBAGAI BAHAN BAKU OLAHAN SOSIS SEBAGAI MAKANAN KHAS KOTA BATAM - Suci Permata Sari; Mulyadi, Tirta (PUSLITABMAS - BATAM TOURISM POLYTECNIC, 2022)
The gonggong snail is one of the marine biota whose distribution is abundant in Indonesia, especially Batam City. The utilization rate of gonggong snails in Batam City has not been maximized due to the lack of public knowledge to process gonggong snails into processed products that have higher economic value. This research was conducted to develop the use of gonggong snails as a new processed product in the food sector that can be used as a business opportunity. Researchers use gonggong snails as raw material for making sausages. This is done to increase the potential of gonggong snails and can become one of the typical foods of Batam City. This type of research is using a pre-experimental design with a one shot case study method. Using two comparison samples of gonggong snail meat and chicken meat as much as them . Data collection techniques using hedonic quality test and hedonic test with research instruments using a questionnaire. The number of panelists as many as 20 people consisting of 5 trained panelists and 15 moderately trained panelists. The data obtained will be analyzed by the Mann Whitney test. The results of the Mann Whitney test showed that there was no significant difference in the taste, color and texture of the gonggong snail sausage, while in scent there was a significant difference. The results of the hedonic test showed that the panelists preferred the taste and scent of the gonggong snail sausage with formulation B , the color that the panelists preferred was the gonggong snail sausage with formulation A, while for the texture of the sausage The panelists Gonggong snails liked both formulations A and B.